Oat Cover Crop Integration in Alfalfa‐Tall Fescue Mixed Grasslands: Optimizing Sowing Ratios and Spatial Arrangements for Enhanced Productivity and Weed Suppression - Zhao, Xiaoyu; Sun, Yuchen; Li, Yuan; Jiao, Yu; Xing, Mengxin; Shi, Jiayu; Yang, Guofeng; Yang, Chao; Tang, Wei; Xu, Yufang; Sun, Juan; Miao, Fuhong (Wiley-Blackwell, 2025)
The integration of cover crops during forage establishment represents a widely adopted agronomic strategy to suppress weed emergence, enhance stand establishment, and improve grassland community stability. In this study, a two-year field experiment (2023–2024) was conducted in Jiaozhou, Shandong Province, China, to evaluate the effects of varying sowing proportions of oat (Avena sativa), employed as a protective cover crop, on forage productivity and weed dynamics in alfalfa (Medicago sativa) and tall fescue (Festuca arundinacea) mixed grasslands. The oat sowing ratios were set at 0%, 15%, 30%, 45%, and 60% in 2023, and subsequently refined to 0%, 10%, 20%, 30%, and 40% in 2024, based on first-year performance. Two spatial configurations (same-row and inter-row sowing) were examined to assess resource partitioning effects. Results demonstrated that inter-row sowing combined with moderate oat inclusion (15%–20%) significantly improved system performance. In 2023, inter-row sowing with 15% oat yielded 16.57 t/ha, while in 2024, inter-row sowing with 20% oat achieved the maximum dry matter yield of 18.4 t/ha. Crude protein concentration also improved by 25.6%, reaching 20.13%. Meanwhile, grass and broadleaf weed biomass decreased by 87.2% and 83.4%, respectively, with total weed biomass and coverage reduced by 64.5% and 60.8%. Additionally, the land equivalent ratio (LER) peaked at 1.48, reflecting a 48% increase in land-use efficiency compared to monoculture systems. Collectively, these findings indicate that incorporating 15%–20% oat as a cover crop, particularly under inter-row sowing patterns, offers a practical and ecologically sound strategy for optimizing forage yield, improving nutritional quality, and achieving robust weed suppression. This approach contributes to sustainable intensification and reduced dependence on chemical herbicides in temperate forage systems.
Keywords: cover crops; forage yield; mixed grasslands; nutritional quality; weed suppression